Consumer Demand and Equilibrium Unemployment in a Working Model of the Customer-Market Incentive-Wage Economy - Phelps, E. S. (Quarterly Journal of Economics, 1992)
Though not conceived as a constant, the natural unemployment rate was taken to be invariant to supply shocks until the late seventies and to real demand shocks until now. The largely micro-theoretic model here is one in a series deriving the natural rate path from general equilibrium. In this model the labor market exhibits generalized real-wage rigidity, resulting from the use of "incentive wages" to combat shirking, and the asset backing shares is the firms' customers, arising from customer-market friction. One finding is that increased consumer demand drives up the natural rate by driving real interest rates up.